Developing a Solution to Utilize Vehicle Dynamics Simulation Tools with a Motion Driving Simulator - Madhava Prakash, Ajit Kumar; Garje Mohankumar, Anup; Misquith, Clive Rahul; Ganatra, Diler Paresh; Soudagar, Irfan Ahmed Khan; Johnsson, Jonas (My University, 2021)
The project develops a method to integrate a CAE software (IPG CarMaker) vehicle model into the CASTER driving simulator. The vehicle dynamics performance is assessed by comparing CarMaker (CM) simulation data against the driving simulator data. First, a baseline generic passenger SUV was modeled on CM with K&C parameters that resemble a real-world vehicle. Then, the driving scenarios and maneuvers such as steady state cornering [6] and double lane change [5] were modeled on CM. Alongside this, IPG Movie and CM for Simulink were used to create real driving scenarios with accurate driving views. Next, the baseline vehicle was simulated in CM and driven on the simulator for both maneuvers. Driver input signals from the driving simulator were fed into CM through CM for Simulink to run the physics of the vehicle model. The output signals computed by CM were fed to the driving simulator to provide motion, audio and visual cues. The integration tool was developed to introduce it in the early phase of vehicle development. The software simulation provides good objective data but no subjective assessment. The use of DIL-simulator is a good method to add subjective assessment in vehicle dynamics development. After every maneuver run, driver’s subjective assessment and rating was recorded. A statistical and graphical comparison of objective data between CM simulation and driving simulator drivers. Analysis of this data showed there is good correlation between results from CM simulations and the driving simulator. Then, vehicle parameter variations were made to understand the vehicle dynamics performance objectively and subjectively. For each model variation, a CM simulation and driving simulator test was carried out by multiple drivers. The vehicle specification variations were designed to produce changes in the steering feel and controllability. This indicates that the driving simulator is a viable supplement to prototype testing, however, further studies must be made to validate the preliminary conclusion. In reality, vehicle evaluations are performed by highly skilled test drivers with accurate subjective assessments. The project yields a tool to develop and evaluate the vehicle dynamics performance. In the hands of a professional driver, this will produce good subjective assessment that ties in with the objective metrics, thus validating it’s use as a cost effective and time efficient tool to develop vehicles.
Keywords: Vehicle Dynamics; CarMaker; Simulink; Simulator; DIL; vehicle testing; subjective assessment; objective metrics; steady state cornering; double lane change; motion platform